PENINGKATAN PRODUKTIVITAS KOLAM LAHAN GAMBUT MELALUI TEKNIK BIOFERTILIZER DAN BAKTERI Azotobacter sp. SERTA Lumbricus Rubellus SEBAGAI ORGANISME DEKOMPOSER - Rhino Pamungkas; Syafriadiman Syafriadiman; Henni Syawal (Berkala Perikanan Terubuk, 2017)
This research was conducted  from September  to December  2016 in the Peat Land Kualu Nenas village, Tambang Subdistrict, Kampar Regency, Riau Province. The aim of this research was to find out the influence and biofertilizer different to increase phytoplankton abudance, and water quality parameters. The method used in this study is an experimental method, using a Complete Random Design (CRD) with four treatments and three replications. The treatments used in this experimental is P0 (without biofertilizer), P1 (human fecal biofertilizer), P2 (cow fecal biofertilizer) and P3 (chicken fecal biofertilizer), the treatments gived Azotobacter and Lumbricus rubellus, 7,88 cfu ml/m2  and 1,2 kg/m2  respectualy. The measure of parameters is type and abundance of phytoplankton, water quality parameter analysis and ground peat, abundance of zooplankton, and chlorophyll-a primary productivity analysis.Result of this research shown that human fecal biofertilizer could increase of ground peat pond productivity. This experiment was prove  the  highest  abundance  total  of phytoplankton  was  113.500  cell.L-1 and chlorophyll-a was 48,859 µg/l. Human fecal biofertilizer could increasethe water quality like pH (6,8), Therm (27-320C), Dissolved Oxygen (3,0-4,83 ppm), Nitrat (4,396-14,059  ppm),  orthophospat  (2,114  – 8,915  ppm).  The analysis  of PCA (Princip   Component   Analysis) shown the physical parameter, chemichal parameter and phytoplankton abundance, the primary productivity. The biplot component was 95,11%. The first component was 75,19%   and the second component was 19,92%.